CRIMINAL POLICY IN CONFLICT INDIGENOUS LAND - Anak Agung Gde Bagus Mahendra Putra; Simon Nahak; I Ketut Widia (NOTARIIL Jurnal Kenotariatan, 2019)
This study aims to analyze the criminal policy in the field of land against customary land conflicts and the criminal policy regarding efforts to overcome conflicts over customary land tenure. The method used is normative legal research with a statutory approach, a library approach, a case approach and a concept approach. The materials used are primary, secondary and tertiary data sources, and then analyzed using legal hermeneutic interpretation techniques. As a result of analysis, it shows that the Criminal Policy in the Field of Land Against Customary Land Conflict is the act of the perpetrators both individually and in groups can result in losses not harmonizing the local indigenous community, there is a criminal nature against the law so that there are perpetrators subject to criminal sanctions in the form of basic penalties namely; as regulated and threatened in Article 10 of the Criminal Code in the form of basic sentences namely the death penalty, imprisonment, confinement and fines and additional penalties for revocation of certain rights, the seizure of certain items and the announcement of a judge's decision. In conclusion, the criminal aspect in every customary conflict is always trailing because usually in customary conflict there are parties who force the will to intersect with customary issues so that they can disturb public order until there is a criminal nature against the law.